Lignin modifying enzyme activities by some Malaysian white rot fungi - Ruqayyah, Tijani I.D.; Jamal, Parveen; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (Africa City of Technology (ACT), 2011)

(untitled)
The possible biotechnological application of ligninolytic enzyme in a range of different fields has stimulated isolation and screening of potential microorganisms from local sources. Twelve white rot fungi (WRF) were isolated from around Gombak area (Malaysia) and sub cultured few times in order to obtain pure cultures. These strains were first screened on solid media plates for their lignin modifying enzymes by using Poly R-478 and ABTS (2, 2’azinobis-(3-ethylbenzothiazoline- 6-sulfonic acid). Of the twelve white rot fungi tested seven were able to decolourize Poly R-478 and eleven showed significant ABTS-oxidation activities. The positive strains were then tested on liquid media for lignin peroxidases (LiP), manganese peroxidases (MnP) and laccase (Lac) activity. Six strains showed potential to secrete all the three enzymes. One strain was able to secrete only two enzymes and five strains secreted only one of the three enzymes.